English Language Teaching in Elementary School: Effective or Not? - Milawati, Milawati (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2019)
Recently curriculum in elementary school has posed the English subject as an extracurricular subject. However, the meeting is done once in a week during effective learning hours. It challenges the English teacher to formulate English learning activities. This study is aimed to describe the teaching-learning activities, including the English teacher’s strategy, material, and media. An English teacher and 29 students of 4A were chosen as the subjects. Mix methods; observation, interviews, and questionnaires were chosen to collect data. The results of observation indicate that the English teacher has the ability in explaining, managing, communicating and evaluating the students. On the contrary, negative responses towards the media used, the attitude, and the benefit of the media were also shown by students’ responses. Mainly, they thought that some of what they get did not match with their expectations. Some changes to create effective English teacher strategy and students’ participation are discussed.